Survey of Dental Implant and Restoration Selection by Prosthodontists in Dubai - Fatma Al Saleh; Moosa AbuZayeda; Sudarat Kiat-amnuay; Alexander Milosevic (Hindawi Limited, 2021)
Background. With various surgical and prosthetic component designs being introduced in dental implants, decisions have to be made when choosing a system and a certain prosthodontic protocol. A survey of implant prosthodontic specialists has not been previously performed in the Middle East. Aim. This study aimed to determine selection criteria and choice of dental implants and restorations by prosthodontic specialists in the Emirate of Dubai, United Arab Emirates. Materials and Methods. A validated 16-item questionnaire was used in the survey which included demographic information, implant training and experience, implant treatment planning, implant restoration, and implant system preference. The research protocol was approved by the Research and Ethics Committees of Hamdan Bin Mohammed College of Dental Medicine and Dubai Health Authority. Prosthodontists were identified from regulatory authority websites and contacted by e-mail with the questionnaire attached. Results. A total of 84.6% (77) of the registered prosthodontists in Dubai completed the questionnaire with 66.2% reported practicing implant dentistry. Out of which, 54.9% reported surgically placing dental implants and 45.1% restore them only prosthetically. Prefabricated metal abutments were the most commonly selected abutments for single crowns (76.0%) and for fixed dental prostheses (66.7%). Screw retention is preferred mostly for single crowns (68.0%) and fixed dental prostheses (74.0%). Locators were the most commonly selected type of attachment for implant-retained/supported overdentures (49.0%). Conventional loading was the most selected type of loading in all oral conditions. Conclusion. Within the limitations of this study, it can be concluded that most prosthodontists in Dubai practice implant dentistry and more than half surgically place dental implants. Prefabricated metal abutments are the most selected type of abutments. Most prosthodontists use screw-retained implant restorations and prefer locator attachments for implant-retained/supported overdentures. Conventional loading is the most preferred implant loading method in all oral conditions. Implant company/system selections are various and there is no major preference for a certain system. The majority of prosthodontists select implant systems based on implant features, literature review, and simplicity of restorative kit.